184k views
2 votes
Find

f(x) + g(x) = (f + g)(x).
Simplify.
f(x) = 5x3 + 5x2 − 6x + 3
g(x) = x3 − 4x2 + x − 2

User Leifg
by
5.4k points

1 Answer

4 votes

I assume you're needing to find
(f+g)(x) given those two functions you have.


\begin{aligned}(f+g)(x) &= f(x) + g(x) \\[0.5em] &= (5x^3+5x^2-6x+3) + (x^3-4x^2+x-2)\end{aligned}

From there, you combine like terms:


\begin{aligned}(f+g)(x) &= f(x) + g(x) \\[0.5em] &= (5x^3+5x^2-6x+3) + (x^3-4x^2+x-2) \\[0.5em] &= 6x^3+x^2-5x+1\end{aligned}

User Tara Prasad Gurung
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.